Driving into floodwater: A systematic review of risks, behaviour and mitigation. (October 2018) - Ahmed, Mozumdar Arifa; Haynes, Katharine; Taylor, Mel
Abstract: This systematic review summarises the findings of research focused on the risks associated with driving into floodwater. The review aims to compare and document the magnitude of the problem internationally; identifying the risk factors; exploring the application of theories and presence of theoretical models to explain people's risky behaviour; and documenting the intervention strategies utilised or proposed. Literature were searched from a number of databases (e.g. PsycInfo, ScienceDirect, Informit) for publication dates to 31 August 2017, then assessed based on their titles, abstracts and full texts and finally 24 articles were selected. This review compares flood fatality data from four countries (Australia, United States, Greece, and Sweden), groups identified risk factors from these selected studies into seven categories, and proposes a holistic integrated intervention model. The results of the review indicate that studies were predominantly conducted in Australia (10 studies) and USA (7 studies). People's decisions to drive into, or turn back from, floodwater are identified as a consequence of both their risk perception and the combined impact of all other factors (e.g. individual, social, environmental etc.) that interdependently contribute to shape decision-making, The theory of Planned Behaviour (TPB) was the only theory that has been utilised within the literature to understand drivers' willingness to take risks. Improving people's decision-making through educational initiatives, advanced structural mechanisms, regulating existing edicts, and regularly evaluating the effectiveness of current strategies are identified as the best approaches to addressing the challenges in this area. Findings suggest that future studies require data and analysis from a larger range of countries, more comparative analyses within and between countries, an exploration of the relationship between risk factors and their relative level of influence and a greater application of behavioural and decision making theories.